Micro-structured medium with large isotropic negative thermal expansion - Cabras, Luigi (Proc Math Phys Eng Sci, 2019)
A challenge in nano- and micro-mechanics is the realization of innovative materials exploiting auxetic behaviour to tailor thermal expansion properties. For this purpose, a new class of micro-structured media possessing an extremely wide range of tunable (positive, negative or even zero) thermal expansion is proposed and analytically and experimentally assessed. For this class of isotropic Mechanical-Auxetic Thermal-Shrinking media, the effective coefficient of thermal expansion is explicitly linked to two microstructural variables via a simple relation, allowing the design with desired values. The theoretical predictions for the negative thermal properties are fully validated by the experimental and numerical outcomes. The simplicity of the proposed structure makes the design useful for the production of a new generation of advanced media, with applications ranging from micromechanical devices to large civil and space structures.